A no power relation: Alterity and the ethics of testimony in Blanchot - Ramírez Zuluaga, Luis Antonio (Estudios de Filosofía, 2017)
This paper develops a theoretical reflection on how a way of a non–determined relation by power appears in Blanchot’s works. First, it shows the way such type of relation emerges in Blanchot’s literary thought, then it sets out its repercussions on an ethical dimension where, on one hand, a “philosophy of separation” is outlined —there, alterity is thought from a relational dissymmetry— and, on the other, an “ethics of testimony” is proposed —from which the responsibility of testifying for those who have suffered an extreme disgrace is assumed.